Mixed convection radiative flow of three dimensional Maxwell fluid over an inclined stretching sheet in presence of thermophoresis and convective condition - M. Bilal Ashraf; T. Hayat; S. A. Shehzad; A. Alsaedi (AIP Advances, 2015)
Three dimensional radiative flow of Maxwell fluid over an inclined stretching surface with convective boundary condition is investigated. Heat and mass transfer analysis is taken into account with thermophoresis effects. Similarity transformations are utilized to reduce the partial differential equations into ordinary differential equations. Series solutions of velocity, temperature and concentration are developed. Influence of different parameters Biot number, therrmophoretic parameter, Deborah number, ratio parameter, inclined stretching angle, radiation parameter, mixed convection parameter and concentration buoyancy parameter on the non-dimensional velocity components, temperature and concentration are plotted and discussed in detail. Physical quantities of interests are tabulated and examined.